Analisis Aspek Pemasaran UMKM Rumah Kripik Kak Yanti di Pematangsiantar - Albenopri Simarmata; Jelita Simbolon; Dina Saragih; Monika Siallagan; Roni Hasibuan; Resna Napitu (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to determine the marketing strategy used by MSMEs "Rumah Kripik Kak Yanti" in JL. Silimakuta. By using descriptive qualitative methods through interviews, and observations, this research provides a comprehensive overview of the marketing aspects of MSMEs "Rumah Kripik Kak Yanti", highlighting the marketing mix consisting of product, price, place, promotion, people, process. as well as providing valuable insights for MSMEs to achieve sustainability and success in a dynamic business environment. The results showed that MSME "Rumah Kripik Kak Yanti" currently uses digital and conventional marketing, and produces a variety of chips products but for the superior product presented by MSME "Rumah Kripik Kak Yanti" is cassava chips, and at an affordable price.